Extracorporeal Circulation Using an Extracorporeal Membrane Oxygenation System and an Autotransfusion System - Yu. A. Bakhareva; Z. Z. Nadiradze; V.N. Medvedev; V. M. Subbotin (Общая реаниматология)
The authors draw attention to the fact that complete cardiopulmonary bypass can be made in the emergency situation in order to perform an extracorporeal membrane oxygenation (ECMO) procedure in a 5-year-old boy weighing 15 kg, diagnosed as having Fallot tetrad. By taking into account the technological features of the system for ECMO, there is an additional need for a blood cell separator to be applied.